A Blockchain-based Secure and Privacy-Preserving Healthcare Data Management Framework with SHA-256 and PoW Consensus - Niu, Geng (Informatica, 2025)
Healthcare systems handle a vast amount of sensitive patient data, making privacy and security crucial concerns. As digital health technologies expand, ensuring accurate and secure data storage becomes increasingly important. However, the frequent exchange of medical information poses risks of unauthorized access and data breaches, complicating secure data sharing. Moreover, many blockchain-based healthcare solutions face challenges related to performance inefficiencies and insufficient privacy safeguards. To overcome these limitations, we introduce a blockchain-powered system designed to enhance privacy protection, secure data sharing, and reliable storage in healthcare environments. Our methodology integrates an access control mechanism using SHA-256 for data integrity, RSA and ECDSA for transaction signatures, and a Proof-of-Work (PoW) consensus mechanism to ensure decentralized trust and scalability. The system employs cryptographic key management with RSA-generated public-private key pairs to secure data access and prevent unauthorized modifications. Experimental results demonstrate that the proposed system achieves an average transaction latency of 15.3 ms for 10 transactions on a single node, with a data integrity success rate of 100% across all tested scenarios. Comparative evaluations against state-of-theart frameworks show our system reduces latency by 39% while maintaining robust security. Additionally, performance analysis highlights the system’s ability to maintain low computational overhead, with transaction times ranging from 25.2 ms to 157.4 ms for 1 to 15 transactions across multiple nodes, ensuring efficient processing in real-world healthcare settings.